Solubilization of insoluble inorganic phosphate by Burkholderia cepacia DA23 isolated from cultivated soil - Song,Ok-Ryul (2008)
A mineral phosphate solubilizing bacterium, Burkholderia cepacia DA23 has been isolated from cultivated soils. Phosphate-solubilizing activities of the strain against three types of insoluble phosphate were quantitatively determined. When 3% of glucose concentration was used for carbon source, the strain had a marked mineral phosphate-solubilizing activity. Mineral phosphate solubilization was directly related to the pH drop by the strain. Analysis of the culture medium by high pressure liquid chromatography identified gluconic acid as the main organic acid released by Burkholderia cepacia DA23. Gluconic acid production was apparently the result of the glucose dehydrogenase activity and glucose dehydrogenase was affected by phosphate regulation.